Enhanced inhibition of bacterial biofilm formation and reduced leukocyte toxicity by chloramphenicol:β-cyclodextrin:N-acetylcysteine complex. (5th November 2016) - Aiassa, Virginia; Zoppi, Ariana; Becerra, M. Cecilia; Albesa, Inés; Longhi, Marcela R.
Graphical abstract: Highlights: Chloramphenicol:β-cyclodextrin: N -acetylcysteine complex was prepared and characterized. The water solubility of chloramphenicol was improved. Toxicity of chloramphenicol in leukocytes was decreased. Antibiofilm activity of chloramphenicol against Staphylococcus was enhanced. The complexes maintained good antibacterial activities in vitro . Abstract: The purpose of this study was to improve the physicochemical and biological properties of chloramphenicol (CP) by multicomponent complexation with β-cyclodextrin (β-CD) and N -acetylcysteine (NAC). The present work describes the ability of solid multicomponent complex (MC) to decrease biomass and cellular activity of Staphylococcus by crystal violet and XTT assay, and leukocyte toxicity, measuring the increase of reactive oxygen species by chemiluminescence, and using 123-dihydrorhodamine. In addition, MC was prepared by the freeze-drying or physical mixture methods, and then characterized by scanning electron microscopy and powder X-ray diffraction. Nuclear magnetic resonance and phase solubility studies provided information at the molecular level on the structure of the MC and its association binding constants, respectively. The results obtained allowed us to conclude that MC formation is an effective pharmaceutical strategy that can reduce CP toxicity against leukocytes, while enhancing its solubility and antibiofilm activity.